Need for Redo Surgery of Maxillofacial Fractures - Thorén, Hanna; Suojanen, Sami; Suominen, Anna Liisa; Puolakkainen, Tero; Toivari, Miika; Snall, Johanna (MDPI, 2025)
The purpose of the present study was to describe the demographic and clinical features of patients having undergone redo surgery for mandibular and/or midfacial fractures and to identify factors that increase the odds of redo surgery. Included were the files of all patients who had undergone open reduction and fixation of one or more mandibular and/or midfacial fracture or orbital reconstructions at the Department of Oral and Maxillofacial Surgery, Helsinki University Hospital, Helsinki, Finland, between 1 January 2013-31 October 2020. Patients having undergone redo surgery were identified, and descriptive characteristics were calculated. In the data analysis, the association between redo surgery and explanatory variables was analyzed. Altogether, 1176 patients were identified for the analysis. Of these, 25 (2.1%) underwent redo surgery for 28 fracture sites. The most common reasons for redo surgery were inadequate fracture reductions of the zygomatic process or the mandible (19 patients) and inadequate orbital reconstructions (four patients). Compared with surgery of only the mandible, combined surgery of the mandible and midface had almost four times greater odds of redo surgery (95% CI 3.8, 0.8-18.4), but the finding was not statistically significant. Although redo surgery was required fairly infrequently, the findings highlight the relevance of surgical competence to treatment success; suboptimal surgical procedure was the most common reason for redo surgery. The literature supports the use of intraoperative CT scanning as a useful tool in association with the treatment of complex midfacial fractures in general and orbital fractures in particular. The success of orbital reconstruction can be promoted by using patient-specific implants.